Histopathological Alterations in Gills, Liver and Kidney of African Catfish (Clarias gariepinus, Burchell 1822) Exposed to Melaleuca cajuputi Extract - Marina Hassan; Anuar Abdalah Nagi Melad; Mohd Ihwan Zakariah; Nor Asma Husna Yusoff (Tropical Life Sciences Research, 2023)
This study evaluated the histopathological changes in the gill, liver and kidney of African catfish (Clarias gariepinus) intoxicated with a sub-lethal dose of Melaleuca cajuputi leaves extract (MCLE) for 96 h. The acute toxicity test has been determined previously with a value of 96-h LC50 = 127 mg/L, hence the selection of sub-lethal ranges from 60 mg/L to 160 mg/L of MCLE. Degenerative alterations were prominent in all tested organs, particularly after exposure to a high concentration of MCLE. Gill exhibited haemorrhage, epithelial lifting, lamellar disorganisation, and necrosis after exposure to a high MCLE concentration. Alterations in the liver include congestion, hydropic degeneration, and vacuolation, whereas lesions in the kidney were pyknosis, vacuolation, hydropic degeneration, and tubular necrosis. The obtained data showed that the organs experienced severe changes proportional to the increase in MCLE concentration. In addition, fish exposed to higher concentrations than the LC50 value experienced irreversible lesions. The present study suggests that the use of MCLE below the LC50 is recommended to avoid severe alterations to organs, particularly in African catfish. This study demonstrated that the use of MCLE above the LC50 promotes severe damage to the gills, liver and kidney of African catfish. However, further investigations are needed to define the causing-mechanisms underlying these effects.